2017
DOI: 10.3390/molecules22112011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Chemical Profiles and Antioxidant Activities of Different Parts of Cultivated Cistanche deserticola Using Ultra Performance Liquid Chromatography-Quadrupole Time-of-Flight Mass Spectrometry and a 1,1-Diphenyl-2-picrylhydrazyl-Based Assay

Abstract: In this study, a sensitive ultra-performance liquid chromatography-photodiode array coupled to quadruple time-of-flight mass (UPLC-PDA-Q/TOF-MS) method and a 1,1-diphenyl-2-picrylhydrazyl (DPPH)-based assay were used to determine the chemical constituents and screen the antioxidant activity profiles of the methanol extracts of different parts of cultivated Cistanche deserticola (C. deserticola). First, qualitative and quantitative chemical composition analyses of the different parts of cultivated C. deserticol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Previous studies have shown that the chemical compounds distribute unevenly in the longitudinal direction of Cistanche deserticola ( 1 ). Therefore, to obtain the same initial contents of chemical compounds in each sample, in the present research all selected Cistanche deserticola was cut into three equal parts for the fresh group (A), steamed without drying group (B), and dried after steaming group (C), respectively, by longitudinal segmentation with the longitudinal symmetry axis as the center ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the chemical compounds distribute unevenly in the longitudinal direction of Cistanche deserticola ( 1 ). Therefore, to obtain the same initial contents of chemical compounds in each sample, in the present research all selected Cistanche deserticola was cut into three equal parts for the fresh group (A), steamed without drying group (B), and dried after steaming group (C), respectively, by longitudinal segmentation with the longitudinal symmetry axis as the center ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…Cistanche deserticola, belonging to the orobanchaceae family, is one of the most famous tonic medicines and is mainly distributed in the tropical and subtropical regions of the world, such as China, Iran, India, Mongolia, and so on (1)(2)(3). Cistanche deserticola serves as one of the most commonly utilized herbal medicines for the treatments of kidney deficiency, impotence, female infertility, morbid leucorrhea, profuse metrorrhagia, and senile (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed a significant decreasing trend from the bottom to the top of cultivated Cistanche deserticola and the highest content in the stems. This combination of metabolomics and antioxidant activity detection promotes the link between composition and activity, which will characterize the quality of CMM by a more comprehensive way and provide a guarantee for clinical efficacy [ 75 ]. Chang et al utilized UHPLC-QTOF/MS combined with PCA and OPLS-DA analysis methods to identify different parts of ginseng, showing significant differences in chemical composition.…”
Section: The Application Of Plant Metabolomics In Quality Evaluation ...mentioning
confidence: 99%
“…In the past 20 years, a series of studies have been conducted to profile the chemical composition of CH because of the benefits from the rapid development of analytical instrumentation. Among diverse available analytical tools, liquid chromatography coupled with tandem mass spectrometry (LC–MS/MS) is the most frequently employed for qualitative analysis 59,77–86 . Obviously, in comparison of phytochemical purifications, more components are usually identified by applying the proposed mass fragmentation pathways to LC–MS/MS datasets.…”
Section: In‐depth Qualitative and Quantitative Analyses Of Chemical Cmentioning
confidence: 99%